Improvement of HVAC system efficiency using an expert system - Noor Muhammad. (2009)
A prototype real-time knowledge based system has been developed to act as an operation and performance aid to help the retrofit process of chiller plant. This system observes the plant data of cooling tower and chiller and gives the optimal operational strategies to achieve maximum energy savings. The system models a 500 TR chiller and is implemented on an engineering workstation using Gensym's G2 object oriented real-time expert system shell. The knowledge acquired for this system has been encoded in the form of engineering models and objects, rules, and mathematical simulations and formulae.